2011
DOI: 10.1007/s00709-011-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid and calcium-induced protection of wheat against salinity

Abstract: Soil salinity is one of the important environmental factors that produce serious agricultural problems. The objective of the present study was to determine the interactive effect of salicylic acid (SA) and calcium (Ca) on plant growth, photosynthetic pigments, proline (Pro) concentration, carbonic anhydrase (CA) activity and activities of antioxidant enzymes of Triticum aestivum L. (cv. Samma) under salt stress. Application of 90 mM of NaCl reduced plant growth (plant height, fresh weight (FW) and dry weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 59 publications
8
34
0
Order By: Relevance
“…On the contrary, Hernandez et al () suggested that Ca addition decreased CAT and APX activities and that the higher salt tolerance observed after Ca addition was due to the protection it exerted on the plasma membrane. In the present study, the activities of CAT and APX increased after Ca addition supporting Al‐Whaibi et al () results and suggesting that Ca addition might directly enhance enzyme activities and decrease oxidative stress and growth inhibition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the contrary, Hernandez et al () suggested that Ca addition decreased CAT and APX activities and that the higher salt tolerance observed after Ca addition was due to the protection it exerted on the plasma membrane. In the present study, the activities of CAT and APX increased after Ca addition supporting Al‐Whaibi et al () results and suggesting that Ca addition might directly enhance enzyme activities and decrease oxidative stress and growth inhibition.…”
Section: Discussionsupporting
confidence: 90%
“…Both CAT and APX activities increased with Ca application. Al‐Whaibi, Siddiqui, and Basalah () reported that Ca application to the solution improved plant growth and enhanced the activities of antioxidant enzymes in Triticum aestivum L. under salt stress. On the contrary, Hernandez et al () suggested that Ca addition decreased CAT and APX activities and that the higher salt tolerance observed after Ca addition was due to the protection it exerted on the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…SA or Ca alone as well as in combination significantly improved proline concentration. 14 The present study investigated whether exogenous SA and Ca 2+ could improve the seed germination of wheat via increasing phenolic contents under salinity stress. A range of plant physiological reactions to SA application are known, but more extensive studies focusing on the effects of SA on phenolic contents under high salinity are still lacking.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, there is an increase in the cytosolic concentrations of Ca 2þ . Interestingly, simultaneous addition of SA and Ca 2þ reduces the NaCl-induced oxidative stress in wheat more effectively by preventing the accumulation of malondialdehyde (MDA) (Al-Whaibi et al, 2012). Raz and Fluhr (1992) reported that in the presence of an exogenous Ca 2þ , SA could induce chitinase formation in tobacco leaves that lack CaM.…”
Section: Introductionmentioning
confidence: 99%